Relational Enhancement: How the Relational Dimension of Social Capital Unlocks the Value of Network-Bridging Ties. (August 2016) - Levin, Daniel Z.; Walter, Jorge; Appleyard, Melissa M.; Cross, Rob
We propose and test a novel approach to the dilemma that the very network-bridging structure most likely to provide access to novel knowledge may be ill-suited for the cooperation needed to successfully transfer that knowledge. We theorize that the relational dimension of social capital (e.g., tie strength) can act as a substitute for the structural benefits of network closure, and so a network-bridging tie yields more value when it is also strong. We further investigate if it is emotional closeness, interaction frequency, or trust that underlies this "relational enhancement" effect. The results from analyzing a bounded network in a large consulting firm and egocentric networks in the engineering division of a large manufacturer provide support for the relational-enhancement effect of tie strength and further identify trust as the key mechanism allowing network actors to unlock the value embedded in their network-bridging ties.